Investigation of electrocrystallisation at the liquid-liquid interface - Ghaheritabrizi, Nazanin (Curtin University, 2024)
This thesis investigates a novel methodology for controlling and studying interfacial crystallization through the application of electrochemistry at the interface between two immiscible electrolyte solutions (ITIES). The research focuses on developing a sophisticated approach to modulate the growth of barium sulfate (BaSO4) crystals by influencing ion-transfer processes at liquid-liquid interfaces.